Chinese universities in the national innovation system : academic entrepreneurship and ecosystem - Yi, Gaofeng (Oxon : Routledge, 2022)
"This book closely examines how universities and higher educational institutions have come to occupy a very significant position in the Chinese national Iinnovation system (NIS) in the last two decades. It looks at the growth, structure and current status of higher education in China and discusses how these world-class institutions are intimately intertwined with the rise of China in the global knowledge economy. It studies themes such as the impact of Chinese universities on industry, business enterprises and national development, relevance of higher education to policies related to industry development, reform measures to improve research intensity and quality of teaching, and internationalization and globalization of higher education. Based on sound empirical research, it also explores concepts like academic entrepreneurship, start-ups and entrepreneurial ecosystems. A key text on the Chinese education sector, the book will be of interest to scholars and researchers of higher education, Chinese studies, science, technology and innovation studies, business economics and management, academic entrepreneurship and public policy."--
Keywords: China -- University based new business enterprises; China -- Technological innovation